Analysis of Nursing Performance and Performance System in Implementing Nursing Assessment in Inaporal Installation Bhayangkara Hospital Pusdik Brimob Gempol Pasuruan - Suhadi; Siyoto, Sandu; Suhita, Byba Melda (Journal for Research in Public Health, 2020)
A hospital is a part of a health facility where the community obtains health services. One of the staff in the hospital who is very influential on the quality of hospital services is nurses with nursing care. This study aims to determine the system of respect for nurses' performance in carrying out nursing care at Bhyankara Hospital, Pusdik Brimob, Watukosek Gempol pasuruan. The samples in this study were 97 nurses who performed nursing care at Bhyankara Hospital, Pusdik Brimob Gempol Pasuruan. The data analysis method used is linear regression. The results showed that the reward system together had a significant effect on nurse performance (n = 67,120; p = 0,000). While partially there is a significant influence between the reward system on nurse performance (n = 9.710; p = 0.023), and between the reward system for nurse performance (n = 5.237; p = 0.000). Whereas the regression equation is Y = 1,721 + 0,518X1 + 1,072X2 + 0,137X3, where Y is the performance, X is the reward system. While the value of Adjusted R Square 0.783 means that the reward system variable affects the performance of nurses by 78.3% while the remaining 21.7% is influenced by other variables not included in this study. Management of Bhyankara Hospital Pusdik Brimob Watukosek Gempol pasuruan needs to do tips to improve the system of rewards and pay attention to other systems that can improve the performance of nurses in carrying out nursing care Improving nurse performance can have an impact on improving the quality of hospital services